2003
DOI: 10.1002/cncr.11262
|View full text |Cite
|
Sign up to set email alerts
|

Empiric risk of prostate carcinoma for relatives of patients with prostate carcinoma

Abstract: BACKGROUND Although narrative reviews have concluded that there is strong support for familial clustering of prostate carcinoma, the association has never systematically been quantified in reviews. The purpose of this meta–analysis was to summarize and quantify the recurrence risk ratio with emphasis on the degree of relation, the specific relationship of the family member, the number of affected family members, and the age at diagnosis. METHODS Publications were identified through computerized database search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
2
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 76 publications
5
108
2
10
Order By: Relevance
“…Results are presented as frequencies, regression coeffi cients or odds ratios (ORs) with 95% CIs (mean differences reported for group comparisons). All analyses adjusted for potential confounding effects of age and geographical location 3 . Table 1 contains demographic information for FDRs and PMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are presented as frequencies, regression coeffi cients or odds ratios (ORs) with 95% CIs (mean differences reported for group comparisons). All analyses adjusted for potential confounding effects of age and geographical location 3 . Table 1 contains demographic information for FDRs and PMs.…”
Section: Resultsmentioning
confidence: 99%
“…Men with a fi rst-degree family history of prostate cancer are at more than double the risk of being diagnosed than men without a family history [ 2,3 ] , although the clinical course is similar for both groups [ 4 ] . Current guidelines on the use of PSA testing for the early detection of prostate cancer recommend that men considering testing should make an informed decision about testing with their health practitioner, taking into account family history [ 5 -12 ] ; with one organisation advising that men with a family history consider testing after the age of 40 years [ 5 ] .…”
mentioning
confidence: 99%
“…The majority (64%) of early onset prostate cancer cases reported a family history of this disease and more than 40% having a confirmed first degree affected relatives of prostate cancer (Lange et al, 2012). Zeegers et al (2003) conducted a meta-analysis based on 33 epidemiologic studies. They found that the risk of developing prostate cancer was almost three times higher for men with affected brothers and father of prostate cancer.…”
Section: Family History Of Prostate Cancermentioning
confidence: 99%
“…Higher risks have been shown for men with two or more affected relatives. [4][5][6][7][37][38][39][40] This increase is too great to be explained by non-genetic factors alone. Analyses based on the Nordic twin registries have found higher risks in monozygotic than dizygotic twins, supporting the hypothesis that much of this familial aggregation is due to genetic factors (42%), rather than shared lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%